Utilização de coordenadas georreferenciadas aplicada à máquinas agrícolas - Gonçalves, Luana de Souza (2017)
In this work, questions about the use of geodetic coordinates for the orientation of agricultural machines and optimization in the soil fertilization process were addressed. For the implementation we use programming techniques in the PIC18F4550 microcontroller and a GPS receiver module (Global Positioning System) that searches satellite data of the geodetic coordinates of an agricultural machine. These coordinates are processed in the microcontroller forming a path that is later compared to a next path obtained in a new displacement of the agricultural machine. The driver receives a light signal if it passes in the same parts of ground that have already applied inputs, in this way, eliminates the overlap that implies additional costs in the application, as well as damages to the culture and the environment. During realization, we realize by testing that the u-blox MAX-7 module is really efficient and meets the requirements in precision farming.